An empirical analysis on electric passenger car adoption among customers in Kerala - Praveen, P. M; Joy, V. S (International journal of economic perspectives, 2025)
Passenger cars are the indispensable transportation vehicle by the family passengers. Passenger cars become so much popular because of its conveniences, comfort and flexibility etc. In the modern society where, people look for more convenient, versatile, freedom and ease of mobility, prefer private transportation method than public transportation which again made the passenger car more popular for the everyday activities like commuting to work, leisure pleasure trip and attending functions, shopping etc. Varied nature of customers’ demands varying requirement in passenger cars like varying in its size from hatchback to spacious sedan, from basic purpose of mobility of passengers to Multipurpose passenger cars. Passenger cars should be equipped with the facilities which enables it to navigate the diverse terrains and road conditions, different life styles and family life cycle, purpose of the commutation etc. Thus, Car manufactures are taking keen interest to adopt latest technologies and features to provide the maximum comfort, safety and performance to customers.